PENGARUH LAMA SENTRIFUGASI SAMPEL URINE TERHADAP HASIL PEMERIKSAAN SEDIMEN LEKOSIT URINE PADA PENDERITA INFEKSI SALURAN KEMIH (ISK)DI LABORATORIUM D-III ANALIS KESEHATAN UNIVERSITAS INDONESIA TIMUR - hijral aswad; Ardiansah Hasin; Chairil Nugraha (Jurnal Media Laboran, 2019)
This research is motivated by the examination of urine sediments as an indication of examination for urinary tract disorders such as urinary tract inflammation or stones in the urinary tract. The organic sediment elements that are meaningful in supporting the diagnosis are cylinders, leukocytes, erythrocytes and epithelial cells. One factor to obtain good results is the concentration of sediment deposits at the bottom of the centrifuge tube obtained by proper centrifugation. The purpose of this study was to find out whether there was an effect of the length of urine sample centrifugation on the results of urine leukocyte sediment examination in patients with Urinary Tract Infection (UTI). This research is a quasi-experimental in the laboratory, the number of treatments carried out in this study were 4 treatments, namely 3 minutes centrifugation, 6 minutes, 9 minutes and 12 minutes. The results showed that after 3 minutes centrifugation, the amount of urine lekocyte sediment averaged 7.17 cells / LPB, after 6 minutes centrifugation an increase in the amount of urine lecocyte sediment was an average of 9.83 cells / LPB. After 9 minutes centrifugation there was an increase in the amount of urine lekocyte sediment by an average of 16.17 cells / LPB, after 12 minutes centrifugation an increase of an average of 20.67 cells / LPB.